A NEW SPECIES OF TELIPOGON (ONCIDIINAE; ORCHIDACEAE) FROM THE PARAMOS OF COLOMBIA - Pérez-Escobar, Oscar Alejandro; Rodriguez, Lizeth Katherine; Martel, Carlos (Phytotaxa, 2017)
Telipogon heinrichsii from the paramo of the western slope of the Central Andean Cordillera in Colombia is proposed as a new species. The new taxon is similar to T. puruantensis and T. vollesii, but differs by the triquetrous peduncle of the inflorescence, a widely ovate labellum, and the column completely surrounded by uniformly distributed setae. A description, illustrations, and notes on the ecology and distribution are provided.